Change in the Status of Secondary Macronutrient Levels in Soil with the Long-term Application of Chemical Fertilizers in Allium ascalonicum L. Plots in Lablare District, Uttaradit Province - Podong, Chattanong; Junta, Saisunee (Asian Health, Science and Technology Reports, 2020)
The long-term use of chemical fertilizers has impacted the levels of secondary macronutrients in agricultural soils in which scallion (Allium ascalonicum L.) crop is grown in Fai Luang sub-district, Lablare District, Uttaradit Province. Accordingly, the objective of this study was to investigate the effects of chemical fertilizer and insecticide use on the content of secondary macronutrients – including calcium (Ca), magnesium (Mg), and sulfur (S) – in the soils from regional scallion plots. The investigation was conducted in 5 villages within the sub-district: Moo 1. Baan Chaing-Saen (Control), Moo 2. Baan Nam-Tum (T1, 50% NPK), Moo 5. Ban Thung-Eang (T2, 100% NPK), Moo 6 Ban Na-Pong (T3, 100% FYK), and Moo 9 Ban Wat Pa (T4, 50 % NPK + 50%FYM). For each of the villages, soil samples from 3 scallion plots were tested for the levels of secondary macronutrients. The total average for each secondary macronutrient levels represented the results. The results are concluded as follows: for the status of change for exchangeable Ca+ average level, it was found that the exchangeable Ca+ average level decreased after every post-harvest period, with the highest control treatment of 45.10% followed by T2 (15.21%), T1 (12.72%), T4 (3.15%) and T3 (2.25%); for the status of change for exchangeable Mg+ average level, it was found that the exchangeable Mg+ average level decreased after every post-harvest period, with the highest control treatment of 19.37%, followed by T2 (13.29%), T1 (7.41%) and T3 (0.38%), but T3 treatment not change status; and for the status of change for exchangeable S average level, it was found that the exchangeable S average level decreased after every post-harvest period, with the highest T3 treatment of 166.67%, followed by T4 (112.50%), T1 (16.67%), but S average level increased in T2 (53.33%) and control (14.29%). Keywords: Chemical fertilizer, Long-term, Allium ascalonicum L., Secondary macronutrients, Uttaradit Province